Emanuel Salomon of Friedberg – Mírohorský and his Memoirs of my life (Theatrum historiae, 2008)
Field-marshal (Feldmarschalleutnant) Emanuel Salomon of Friedberg – Mírohorský (1829-1908) was not only a soldier, but also a Czech patriot, artist and writer. He contributed to our knowledge of the life in Austrian army of „long 19 century“. He was one of few Czechs who gained very important position in Austrian army in 19 century. He left behind a large manuscript under the title Memoirs of my life (Paměti z mého žití). It has more than 6500 pages and it is a valuable source to the political, social and cultural history of 19 century.